2013
DOI: 10.1371/journal.pone.0056795
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Human Cytomegalovirus Proteins and Nucleic Acids in Primary Breast Cancer and Metastatic Sentinel Lymph Nodes

Abstract: BackgroundBreast cancer is a leading cause of death among women worldwide. Increasing evidence implies that human cytomegalovirus (HCMV) infection is associated with several malignancies. We aimed to examine whether HCMV is present in breast cancer and sentinel lymph node (SLN) metastases.Materials and MethodsFormalin-fixed paraffin-embedded tissue specimens from breast cancer and paired sentinel lymph node (SLN) samples were obtained from patients with (n = 35) and without SLN metastasis (n = 38). HCMV immedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
126
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 129 publications
(142 citation statements)
references
References 50 publications
9
126
2
Order By: Relevance
“…[5] However, we found that HCMV wasn't associated with tumor recurrence or patient death. The virus wasn't detected in non -tumor tissue or inflammatory cells in our study which is consistent with the results detected by Taher et al [31] In addition, others didn't find the virus in the fibroadenoma tissue. [19] EBV has been suggested to be associated with breast cancer indicated by detection of the virus in breast milk, presence of some EBV associated lymphomas in the breast and that breast cancer has epidemiological similarities to young adult Hodgkin's lymphoma.…”
Section: Published By Sciedu Presssupporting
confidence: 91%
See 1 more Smart Citation
“…[5] However, we found that HCMV wasn't associated with tumor recurrence or patient death. The virus wasn't detected in non -tumor tissue or inflammatory cells in our study which is consistent with the results detected by Taher et al [31] In addition, others didn't find the virus in the fibroadenoma tissue. [19] EBV has been suggested to be associated with breast cancer indicated by detection of the virus in breast milk, presence of some EBV associated lymphomas in the breast and that breast cancer has epidemiological similarities to young adult Hodgkin's lymphoma.…”
Section: Published By Sciedu Presssupporting
confidence: 91%
“…Others found the virus proteins in 100% of cases and in the epithelial cells of metastasis in the sentinel lymph nodes suggesting its role in development of breast cancer and its metastasis. [31] It has been found that there is an association between HCMV and lower disease free and overall survival times. [5] However, we found that HCMV wasn't associated with tumor recurrence or patient death.…”
Section: Published By Sciedu Pressmentioning
confidence: 99%
“…HCMV has increasingly been implicated as an etiological agent in oncogenesis. HCMV genes have been found in a variety of human carcinomas but not in matched tissue controls (31)(32)(33)(34). HCMV nucleic acids and proteins have also been found to be associated with a high percentage of malignant gliomas and meduloblastomas (35)(36)(37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…Human cytomegalovirus (HCMV) has been detected in glioblastoma multiforme 14,15 , medulloblastoma 16 , neuroblastoma 17 , colon cancer 18,19 , and prostate cancer 20 , as well as in primary BC and sentinel lymph nodes and distant metastases from BC patients [21][22][23] . In general, increased viral activity is associated with worse prognosis.…”
Section: Introductionmentioning
confidence: 99%